2007
DOI: 10.1158/0008-5472.can-07-3028
|View full text |Cite
|
Sign up to set email alerts
|

Cells Deficient in the FANC/BRCA Pathway Are Hypersensitive to Plasma Levels of Formaldehyde

Abstract: Formaldehyde is an aliphatic monoaldehyde and is a highly reactive environmental human carcinogen. Whereas humans are continuously exposed to exogenous formaldehyde, this reactive aldehyde is a naturally occurring biological compound that is present in human plasma at concentrations ranging from 13 to 97 Mmol/L. It has been well documented that DNA-protein crosslinks (DPC) likely play an important role with regard to the genotoxicity and carcinogenicity of formaldehyde. However, little is known about which DNA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
151
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 164 publications
(163 citation statements)
references
References 19 publications
11
151
1
Order By: Relevance
“…Recently, the DNA damage response to FA was assessed using chicken DT40 cells with targeted mutations in various DNA repair genes (59). The DT40 cells deficient in HR and TLS were hypersensitive to FA, and those deficient in NER and BER were moderately to slightly sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the DNA damage response to FA was assessed using chicken DT40 cells with targeted mutations in various DNA repair genes (59). The DT40 cells deficient in HR and TLS were hypersensitive to FA, and those deficient in NER and BER were moderately to slightly sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…The defective DNA repair capacity of FA stem cells may underlie their hypersensitivity to endogenous DNA damage, such as damage from ROS (15,99) or from serum formaldehyde (100,101). Such hypersensitivity may lead to decreased hematopoietic cellularity (stem cell loss in early development), similar to phenotypes observed in ATM-deficient or ligase IV-deficient (LIG4-deficient) mice (102,103).…”
Section: Future Of Fa Therapymentioning
confidence: 99%
“…Using a mutant cell panel derived from the chicken DT40 cell line, it was shown that cells lacking Fancd2 or Brca2 are particularly sensitive to formaldehyde at concentrations similar to those in normal human serum (Ridpath et al 2007). Patel and coworkers indicated in a series of papers that aldehyde detoxifying enzymes ALDH2 (which mainly catalyzes acetaldehyde) and ADH5 (which mainly catalyzes formaldehyde) play critical roles in FA model mice in the suppression of bone marrow failure and leukemogenesis (Langevin et al 2011, Garaycoechea et al 2012, Oberbeck et al 2014, Pontel et al 2015.…”
Section: Therapeutic Implications Of Hr Defects In Hbocmentioning
confidence: 99%